Perancangan Evaluasi Mandiri Berbasis Komputer Dengan Metode Pengacakan Bank Soal Pada Materi Jaringan Komputer 1 Menggunakan Actionscript 2.0 - Dhany Faizal Racma (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2015)
This design aims to develop the software of self-evaluation computer based for Networking 1 course on Information System department. The methods are used is carried out by the methods of research and development (R & D), that refers to the model of ADDIE (Analysis, Design, Development, Implementation, Evaluation). Software is developed based on Adobe Flash using ActionScript 2.0 programming language. Self-evaluation computer based has through the test limited by college student with percentage 95,15%. Continues with field trials to extensively college student with achievement of each percentage is 90,15% by college student. At the end of this development, generated self-evaluation computer based for Networking 1 course equipped with random method of the question bank of packages and accompanied with output result from the self-evaluation computer based.